Pengaruh Kualitas Pelayanan Terhadap Loyalitas Anggota BMT Mardhatillah Berkah Cabang Purwakarta - Siti Rohmat; Saepul Bahri (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2018)
The purpose of this study is to determine the influence of Service Excellent To Savings Loyalty On Members BMT Mardhatillah Berkah Branch Purwakarta. In this study, the object of research is the Savings and Loans Cooperative BMT Mardhatillah Berkah Branch Purwakarta. This research is included into descriptive research. Primary data collection through questionnaires with sample determination using Probability Sampling technique. Data analysis techniques used in this study is the validity of data, data reliability, data normality, data heterokedastisitas. While the test design using linear regression data analysis, correlation coefficient, coefficient of determination. The results showed that Service Excellent has a significant effect on Member Loyalty At Baitul maal wat tamwil Mardhatillah Berkah Branch Purwakarta. This is seen from the results of hypothesis testing where the value 14.121 (t count)> 1.66 (t table). With the level of significance is 0.000 smaller than 0.05. The correlation coefficient value of 0.776 and the coefficient of determination = 60.2%. Furthermore, the rest is influenced by other variables not examined in this research.